The mechanism of antimalarial action of ellagic acid on haemoglobin metabolism in plasmodium falciparum - Thuduhena, Thuduhenage Dona Anjana Chamilka (2024)
Malaria caused by Plasmodium parasites has afflicted humans since ancient times. Due to the prevalence of drug-resistant P. falciparum, the effectiveness of the standard antimalarial drugs has decreased, requiring research into the development of new antimalarial drugs with novel targets. Ellagic acid has been shown to have antimalarial activity against P. falciparum in vitro by inhibiting the formation of beta-haematin (haemozoin) in the mature stage parasite. The present study aimed to elucidate the mechanism of antimalarial action of ellagic acid on haemoglobin ingestion, transport and digestion in chloroquine-sensitive (3D7) and chloroquine-resistant (W2) strains of P. falciparum in vitro. The antimalarial activity of ellagic acid that inhibits 50% of the parasite population (IC50) was determined using a malarial SYBR Green I fluorescence-based (MSF) assay with artemisinin was used as a standard drug. Based on the IC50 value of ellagic acid, early trophozoite stage parasites were incubated with the compound at different concentrations for 8 hours before Giemsa-stained thin blood smears were prepared and viewed by light microscopy. The concentrations of 3.0 and 3.9 nM were selected to observe the maximum effect of ellagic acid on early trophozoite stage of 3D7 and W2 parasites, respectively by transmission electron microscopy. Jasplakinolide (7 μM) and E-64 (10μM) were used as control drugs. The results show that ellagic acid significantly inhibited (p < 0.001) 3D7 and W2 parasites with IC50 values of 1.0 ± 0.7 and 1.3 ± 0.1 nM, respectively as compared with artemisinin (IC50-3D7 parasite = 2.2 ± 0.2 nM; IC50-W2 parasite = 4.3 ± 0.3 nM). The results show that shrunken parasites were observed in all ellagic acid-treated groups of 3D7 and W2 parasites. The results show the formation of 3D7: 3 ± 2 and W2: 4 ± 2 haemoglobin-containing cytostomal sections, indicating the inhibition of haemoglobin uptake in the ellagic acid-treated 3D7 and W2 parasites. Only 3 ± 1 cytostomal sections were observed in the jasplakinolide-treated 3D7 parasite, 2 ± 1 cytostomal section was observed in the jasplakinolide-treated W2 parasite. The haemoglobin-containing transport vesicle was not observed in the ellagic acid and jasplakinolide-treated 3D7 and W2 parasites. As compared with the control of non-treated parasites, the high contrast and enlarged digestive vacuole was observed in the ellagic acid and E-64-treated 3D7 and W2 parasites. In conclusion, ellagic acid has the potential to be a new antimalarial drug targeting haemoglobin ingestion, transport and digestion of chloroquine-sensitive and chloroquine-resistant strains of P. falciparum.